Effect of Price, Promotion and Product Quality on Consumer Satisfaction Kentucky Fried Chicken (KFC) Quality Rantauprapat - Riski Wahyuni; Bayu Eko Broto; Fauziah Hanum (Budapest International Research and Critics University, 2022)
This study was conducted to determine and analyze the effect of price, promotion and product quality on consumer satisfaction. The design of this research is hypothesis testing using primary data obtained by distributing 100 questionnaires to consumers of Kentucky Fried Chicken (KFC) Quality Rantauprapat, with the measuring scale used is the Likert scale. In this study, the data analysis technique used is the multiple linear regression analysis technique of quantitative data using the (SPSS) method. The results of this study conclude that partially and simultaneously there is a positive effect but not all significant between the effect of price, promotion and product quality on consumer satisfaction of Kentucky Fried Chicken (KFC) Quality Rantauprapat.